Lichen sclerosus and acute urinary obstruction. Issue 3 (June 1992) - Hawkswell, J; Nathan, M
Abstract : A case of acute urinary obstruction due to early lichen sclerosus disease is described. In this case both histological corroboration and efficacy of potent topical steroid have been beneficial.